SYNTACTIC PROPERTIES OF INTERROGATIVE PRONOUNS IN ENGLISH (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article examines the syntactic attributes of interrogative pronouns in the English language. These pronouns are pivotal in interrogative sentence formation and information inquiry. By conducting a thorough examination of their syntactic characteristics, this research endeavors to elucidate their structural features and utilization tendencies. Employing a blend of theoretical linguistic frameworks and corpus-based investigation, the study delves into multiple facets of interrogative pronouns. The outcomes enrich comprehension concerning the operational dynamics of these pronouns within the framework of English language usage.